Green oriented procurement for building projects: Preliminary findings from Malaysia. (1st April 2017) - Bohari, Asmah Alia Mohamad; Skitmore, Martin; Xia, Bo; Teo, Melissa
Abstract: As Malaysia is planning an increasing number of construction projects in the near future, a major imperative is to embark on a 'greener path' to ensure a more sustainable future. One of the efforts currently being undertaken is the introduction of green procurement, which is part of the government's MyHijau initiative and highlighted in the Malaysian economic planning program. Previous studies have found that the concept of green procurement is still very new to the Malaysian construction industry and accordingly have sought to address the low levels of knowledge in this area. This paper presents preliminary findings of green procurement practices in Malaysia based on a review of the existing literature as well as a pilot study utilising semi-structured interviews of experienced practitioners. Our findings indicate that, although the term 'green procurement' is not being used broadly across construction stakeholders, some green practices related to procurement are developing in the industry. These include the availability of green procurement guidelines and the inclusion of green criteria in the tender process, with due consideration given to green purchasing. The findings are encouraging and point to an increasing awareness, practices and implementation of green procurement by practitioners in Malaysia. It is envisaged that the paper will provide the basis for future research into green procurement practices for construction projects in Malaysia and beyond.